Vozes e narrativas dos egressos 2019 da Licenciatura em Pedagogia diurno da UFSM sobre a formação inicial no contexto curricular das disciplinas de Educação Matemática - Ponciano, Paula Aparecida Cavalheiro (2023)
This investigative proposal emerged from two trajectories, practical and experiential during my training as a Graduate in Pedagogy. The first is the compulsory curricular internship experienced in the 4th year of Elementary School (PE) in a Municipal School of Santa Maria. The second disposes of my practice as a teacher who teaches Mathematics in the municipality of Santo Augusto in the initial years in the period of the 2nd semester of 2019. Therefore, the objective is to analyze the curriculum of mathematics of the early years in the formation of Pedagogos (as) of UFSM. For this, the research has a qualitative methodological basis, bibliographical and documentary review, including the participation of graduates of the year 2019 of the Degree Course in Pedagogy of UFSM from an open questionnaire. In short, we analyzed the process of formation of these pedagogos and brought the narratives of experiences lived by these subjects during the curricular internship in Mathematics - initial years. In the course of the analysis, we focused on the reflections of these experiences in relation to pedagogical practices in the Teaching of Mathematics of the early years of PE. Then, we divided these discussions and analyzes in the following sessions: experiences of the graduate in Pedagogy in basic education with Mathematics; experiences of the graduate in Pedagogy in the Compulsory Curricular Internship with the discipline of Mathematics in the early years of PE; Significant Learning in training as a Pedagogue in the Course with the disciplines of Mathematics in the early years of PE and Mathematics Education under the vision of these Graduates in Pedagogy. Thus, we seek an intermediate between the practices and theories about the Formation of the Pedagogue through this investigative analysis and which meanings, narratives and paths can contribute to the formation of Pedagogues and the duality of teaching and learning Mathematics Education.